Franges intra-urbaines à l’épreuve des projets de paysage - Émeline Bailly (Projets de Paysage)
With diffuse urban sprawl on the outskirts of urban centres, urban fringes are shifting and becoming less easily distinguishable. They are diffused within the urbanisation process and take different forms within the agglomeration itself. Our assumption is that these fringes cannot be simply considered as the edges of the agglomeration but rather as intermediary territories, blurred spaces between spatial, social and conceptual realities that landscape planning can reconcile. They constitute interstices which are able to underscore the discrete component entities of the city with their urban characteristics and distinct landscapes. Thus, in landscape projects intra-urban fringes may be considered, in their different configurations, as opportunities for providing singular urban experiences and as landscape components revealing different urban landscapes and the impressions associated with them.